Hypertension In The Elderly In The Work Area Of Sawah Lebar Community Health Center, Sawah Lebar Baru Village Rt 23, Ratu Agung District, Bengkulu City - Ermakris Adelina; Yunita, Erma; Winarnni, Yesi (Jurnal Inovasi Kerja Nyata, 2025)
Hypertension is the measurement of systolic and diastolic blood pressure that continuously exceeds normal values. The prevalence of hypertension in Indonesia based on measurements of the population aged 18 years is 34.1%. Hypertension occurs in the age group 31-44 years 31.6%, 45-54 years around 45.3%, and at the age of 55-64 years 55.2%. The prevalence of hypertension in Indonesia is 34.1%. Bengkulu Province nationally ranks 26th at 28.14%, with an estimated number of cases ≥15 years. In Bengkulu City, the incidence of Hypertension is quite high, there are Hypertension Cases, especially in the area of ​​Sawah Lebar a lack of a healthy lifestyle. The 2025 Thematic Community Service Program (KKN-T) of Dehasen University Bengkulu focuses on efforts to prevent hypertension and distribution of leaflets. This activity was carried out through collaboration with RT officials and the local community. Cross-sector collaboration and ongoing education are very important to support efforts to reduce the incidence of hypertension by improving the health of the elderly.